Association between excreta management and incidence of extended-spectrum β-lactamase-producing Enterobacteriaceae: role of healthcare workers' knowledge and practices. Issue 1 (May 2019) - N'Guyen, T.T.H.; Bourigault, C.; Guillet, V.; Buttes, A-C. Guille des; Montassier, E.; Batard, E.; Birgand, G.; Lepelletier, D.
Summary: Background: The spread of extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-PE) in healthcare environments has become a major public health threat in recent years. Aim: To assess how healthcare workers (HCWs) manage excreta and the possible association with the incidence of ESBL-PE. Methods: Eight hundred HCWs and 74 nurse-supervisors were questioned through two self-report questionnaires in order to assess their knowledge and practices, and to determine the equipment utilized for excreta management in 74 healthcare departments. Performance on equipment utilized, knowledge and practices were scored as good (score of 1), intermediate (score of 2) or poor (score of 3) on the basis of pre-established thresholds. Linear regression was performed to evaluate the association between HCWs' knowledge/practices and the incidence of ESBL-PE. Findings: Six hundred and eighty-eight HCWs (86%) and all nurse-supervisors participated in the survey. The proportions of respondents scoring 1, 2 and 3 were: 14.8%, 71.6% and 17.6% for equipment; 30.1%, 40.6 % and 29.3% for knowledge; and 2.0%, 71.9% and 26.1% for practices, respectively. The single regression mathematic model highlighted that poor practices (score of 3) among HCWs was significantly associated with increased incidence of ESBL-PE ( P =  0.002). Conclusions: A positive correlation was found between HCWs' practices for managing excreta and the incidence of ESBL-PE, especially in surgical units. There is an urgent need for development of public health efforts to enhance knowledge and practices of HCWs to better control the spread of multi-drug-resistant bacteria, and these should be integrated within infection control programmes.